2021
DOI: 10.3390/molecules26154659
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of CeO2 Nanoparticles from the Abelmoschus esculentus Extract: Evaluation of Antioxidant, Anticancer, Antibacterial, and Wound-Healing Activities

Abstract: Metal oxide nanoparticles synthesized by the biological method represent the most recent research in nanotechnology. This study reports the rapid and ecofriendly approach for the synthesis of CeO2 nanoparticles mediated using the Abelmoschus esculentus extract. The medicinal plant extract acts as both a reducing and stabilizing agent. The characterization of CeO2 NPs was performed by scanning electron microscopy (SEM), X-ray diffraction (XRD), ultraviolet-visible spectroscopy (UV-Vis), and Fourier transform in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 49 publications
(58 reference statements)
1
37
0
Order By: Relevance
“…At a low of CeO 2 -NP concentration (25 µg/ml), cells begin to shrink and, similarly, with increasing concentration (75 µg/ml), there are further changes in cell morphology suggestive of apoptosis. At a concentration of 100 µg/ml, cancer cells exhibit increased apoptosis[ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a low of CeO 2 -NP concentration (25 µg/ml), cells begin to shrink and, similarly, with increasing concentration (75 µg/ml), there are further changes in cell morphology suggestive of apoptosis. At a concentration of 100 µg/ml, cancer cells exhibit increased apoptosis[ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…This might have been related to the fact that miR129 has not been reported to exhibit antibacterial activity, but CeO 2 has been reported to have good antibacterial activity. A study by Ahmed [ 10 ] study has shown that the antibacterial efficacy of CeO 2 -NPs against sea anemones largely depends on the NP concentration. As the concentration increases, the inhibition range also increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an antimicrobial and treatment for many disorders, CeO2NPs have been used. When it comes to the treatment of osteosarcoma and other bone cancers, CeO2NPs have been most often employed [69]. Because of their low toxicity and capacity to induce cancer cells to apoptosis or necrosis, these nanoparticles could be used as an effective treatment for cancer-antioxidant activity in CeO2NPs obtained from Origanum majorana as well as Ceratonia siliqua [70].…”
Section: Applications Of Cerium Oxide Nanoparticles In Cns Disordersmentioning
confidence: 99%
“…The study plan uses a series of composite nanofibrous scaffolds composed of PU/PVA-Gel incorporated with CEO to potentiate the cell proliferation of NFs loaded with a low dose of nanoceria (nCeO 2 ). Nanoceria at 1–2% was reported for its efficiency as a cell proliferative agent used for tissue regeneration [ 41 , 42 , 43 ]. Below this concentration, the efficiency of nCeO 2 as a proliferative agent is reduced.…”
Section: Introductionmentioning
confidence: 99%